The Effectiveness of Learning Instrument of Multiple Representations-Based Inquiry Model to Train Critical Thinking Skills in Physics Lesson - Amanati, Anis (JPPS (Jurnal Penelitian Pendidikan Sains), 2020)
This research was motivated by the lack of student critical thinking skills in physics. Two factors influencing physics learning achievement are internal factors consisting of verbal skills and abstraction, and external factors consisting of curriculum, learning method, facilities and infrastructure, as well as the accuracy of selecting teaching media/material. Multiple representations-based inquiry learning model allows student to express a concept in various form including verbal, graph, and mathematics. This learning model has been applied on 30 graders X-IPA in SMA Kemala Bhayangkari 1 Surabaya where their average pretest score was 31.11. After they participated in three physics lessons, by using a learning model and instruments with multiple representations-based inquiry approaches, their critical thinking skill is improved significantly become 82.67. Besides that, 87.6% of student likes the learning implemented on them. It could be concluded that learning instruments of multiple representations-based inquiry stated effective to train student critical thinking skills on physics of high school.